Evaluation of the ductility demand in partial strength steel structures in seismic areas using non-linear static analysis - Nogueiro, Pedro (2011)
The performance of a structural system can be evaluated resorting to non-linear static analysis, also commonly referred to as Pushover Analysis, because of the nature of application of lateral loads while defining the capacity of the structure. This analysis involves the estimation of the structural strength and deformation demands and the comparison with the available capacities at desired performance levels. This paper aims at evaluating the seismic response of three steel structures using non-linear static analyses, based on the N2 method, adopted by Eurocode 8, the European seismic code. The results are compared with the ones evaluated by means of non-linear dynamic analyses. As a conclusion it can be ascertained that the non-linear static procedures are an alternative tool in seismic assessment and design, over just a force-based design. For structures that vibrate mainly in the fundamental mode, the pushover analysis applied in this work will provide good estimates of global, as well as local inelastic deformation demands.